Amoris Laetitia : Exhortación apostólica postsinodal sobre el amor en la familia - Francis, Pope, 1936- (EDICIONES UC, 2016)
The joy of love (Amoris laetitia) delves into the conclusions of the Synods of Bishops, held between 2014 and 2015, whose objective was to dialogue around the main issues that currently concern the family. With the purpose of broadening the gaze of the whole Church and highlighting the value of marriage and the family, Francis introduces the document with an invitation to begin a path to deepen "with freedom" in the different situations. With this, he delves into his own way to deliver teaching, giving great space to conscience and personal discernment, both to pastors and to laity, calling for the search for "more inculturated solutions, attentive to local traditions and challenges."